Towards the Strategic Alignment of Corporate Services with IT, applying Strategic Alignment Model (SAM) - Belalcázar Villamar, Alberto (2016)
In a context of increasingly demanding and eager users for the use of the technology, the areas of information and communications technology (ICT) acquire a leading role in the organizations due to the support and input that they provide. The constant and innovative growth of ICT generates in the organizations a difficult dynamic to align with their strategic objectives. This causes a gap among the strategy, the corporate objectives of the organization and the administration of IT services. In this article, a conceptual framework is proposed from a heuristic point of view concerning to the alignment of business processes with IT, using and modifying the Strategic Alignment Model (SAM) of Henderson and Venkatraman in order to achieve a value chain implemented through requests and services with the aim of aligning the strategies of the Corporate Governance, Enterprise Governance and IT Governance. A case study is presented to display how a corporate request is transformed into an IT request within the framework of the strategic objectives.